Impact of Gluten Withdrawal on Health-Related Quality of Life in Celiac Subjects: An Observational Case-Control Study - Tontini, Gian Eugenio; Rondonotti, Emanuele; Saladino, Valeria; Saibeni, Simone; de Franchis, Roberto; Vecchi, Maurizio (Digestion, 2010)
Aims: To evaluate health-related quality of life (HRQoL) in celiac disease (CD) patients at the time of diagnosis and during a gluten-free diet (GFD). Patients and Methods: We enrolled 43 adult CD patients (18 with a typical and 15 with an atypical clinical presentation, and 10 with dermatitis herpetiformis, DH) and 86 age- and sex-matched healthy controls. We administered the Short Form 36 Health Survey (SF-36) questionnaire at diagnosis and after 1, 12 and 24 months of a GFD. Results: At the time of diagnosis CD patients showed significantly lower SF-36 scores than controls; this figure was observed in women but not in men. At baseline, both typical and atypical CD patients had lower SF-36 scores than controls, while DH patients showed a SF-36 profile comparable to that of controls. During a GFD the SF-36 scores improved continuously in CD patients and in the female subgroup, becoming similar to those of matched controls at 1-year follow-up. After gluten withdrawal typical and atypical CD patients improved their SF-36 scores and reached values comparable to those of controls. Conclusions: At diagnosis, CD patients perceived a poor HRQoL; this figure appears to be mostly associated with female gender. In all subgroups of CD patients with a low HRQoL at diagnosis, the GFD allowed progressive restoration of HRQoL perception.